Children’s Rights in Regional Human Rights Systems - Kata Zsófia Prém, Laura Kovács-Berényi; Raisz, Anikó (2024)
Children’s Rights in Regional Human Rights Systems aims at exploring human rights protection of children throughout the world from the most effective international perspective: the regional human rights systems. These systems tend to function attached to a community of states, usually in the form of a sui generis international organisation. These conglomerates are in certain ways deemed to be more efficient than universal ones as the given community not only consists of a fewer number of states, but also shares certain basic values or objectives which are particularly useful when talking about putting children’s rights (but also in general human rights) into reality.The present volume focuses on the dedicated children-related human rights instruments of the Council of Europe, the Organization for Security and Co-operation in Europe, the European Union, the Organisation of American States, and the African Union furthermore including the human rights frameworks of the Community of Independent States, the Arab League, and the Islamic Conference as well.The main objective is to make the readers familiar with the protection of children’s rights not only in Central Europe, but also on other continents, as through the interaction of these systems we have already learnt important lessons from each other.